2022
DOI: 10.3389/fmolb.2022.850559
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Neurodevelopmental Disorders Linked to CK2: Okur-Chung Neurodevelopmental Syndrome and Poirier-Bienvenu Neurodevelopmental Syndrome—Two Sides of the Same Coin?

Abstract: In recent years, variants in the catalytic and regulatory subunits of the kinase CK2 have been found to underlie two different, yet symptomatically overlapping neurodevelopmental disorders, termed Okur-Chung neurodevelopmental syndrome (OCNDS) and Poirier-Bienvenu neurodevelopmental syndrome (POBINDS). Both conditions are predominantly caused by de novo missense or nonsense mono-allelic variants. They are characterized by a generalized developmental delay, intellectual disability, behavioral problems (hyperact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…For POBINDS, Bonanni et al very recently reviewed the available literature, where they correlate the neurodevelopmental abnormalities to epilepsy severity and highlight the heterogeneity of the clinical phenotypes that have been associated with the CSNK2B gene ( Bonanni et al, 2021 ). A recent article has reviewed both diseases ( Ballardin et al, 2022 ). Broader phenotype-genotype correlation data will help us understand the severity of the diseases and may lead to a specific differential diagnosis to clearly identify OCNDS and POBINDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For POBINDS, Bonanni et al very recently reviewed the available literature, where they correlate the neurodevelopmental abnormalities to epilepsy severity and highlight the heterogeneity of the clinical phenotypes that have been associated with the CSNK2B gene ( Bonanni et al, 2021 ). A recent article has reviewed both diseases ( Ballardin et al, 2022 ). Broader phenotype-genotype correlation data will help us understand the severity of the diseases and may lead to a specific differential diagnosis to clearly identify OCNDS and POBINDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of OCNDS patients exhibit growth problems such as microcephaly and reduced weight and stature (24). We observed that male and female K198R mice weighed 16.07% and 17.6% less, respectively, at 14 weeks of age, a difference that increases with age for males reaching nearly 33.9% at 16 months (fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Ballardin et al. (2022) suggested that variants in the zinc finger and/or C‐terminal structural domains appear to have a more severe phenotype than variants in the N‐terminal region in patients with POBINDS. Meanwhile, Li et al.…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al (2022) and Li et al (2019) suggested that variants in zinc finger structural domain cause a milder POBINDS phenotype and that epilepsy is more easily controlled. In contrast, Ballardin et al (2022) suggested that variants in the zinc finger and/or C-terminal structural domains appear to have a more severe phenotype than variants in the N-terminal region in patients with POBINDS. Meanwhile, Li et al (2019) proposed that the zinc finger structural domain is a hotspot variant region of CSNK2B.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation